2020
DOI: 10.1063/5.0003428
|View full text |Cite
|
Sign up to set email alerts
|

Understanding attenuated solvent reorganization energies near electrode interfaces

Abstract: In this manuscript, we examine the role of image charge effects on the electrostatic potential fluctuations experienced by ionic species in the vicinity of an electrode surface. We combine simulation and theory to quantify these fluctuations and how they vary with distance from the electrode surface. We observe that the potential distribution narrows significantly for species within a few electrolyte screening lengths of the electrode. We attribute this narrowing to the effects of image charge fluctuations ori… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
17
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 13 publications
(18 citation statements)
references
References 27 publications
1
17
0
Order By: Relevance
“…In addition, while spectator cations and anions have been used extensively to alter the reaction rates of homogenous and heterogeneous reactions for the redox of metal complexes, their role on the reorganization energy has been rarely reported even though the reaction rate scales inversely with the reorganization energy in the Marcus theory , for homogeneous electron-transfer reactions or the Marcus–Hush–Chidsey (MHC) formalism , for heterogeneous (faradic) reactions at electrodes. The solvent reorganization energy of heterogeneous electron-transfer reactions has been shown to decrease as the redox centers move closer to the electrode surface, , which is in agreement with models based on the dielectric continuum theory, predicting a decrease in the electron-transfer reorganization energy with decreasing distance between the redox center and the electrode, , as well as classical molecular dynamics (MD) simulation . Moreover, while previous Raman and Fourier transform infrared (FTIR) spectroscopy studies have shown that the solvation structure of the redox species in bulk can be altered by spectator cations, much remains to be understood about how they influence the solvation environment at the electrified interface.…”
Section: Introductionsupporting
confidence: 78%
“…In addition, while spectator cations and anions have been used extensively to alter the reaction rates of homogenous and heterogeneous reactions for the redox of metal complexes, their role on the reorganization energy has been rarely reported even though the reaction rate scales inversely with the reorganization energy in the Marcus theory , for homogeneous electron-transfer reactions or the Marcus–Hush–Chidsey (MHC) formalism , for heterogeneous (faradic) reactions at electrodes. The solvent reorganization energy of heterogeneous electron-transfer reactions has been shown to decrease as the redox centers move closer to the electrode surface, , which is in agreement with models based on the dielectric continuum theory, predicting a decrease in the electron-transfer reorganization energy with decreasing distance between the redox center and the electrode, , as well as classical molecular dynamics (MD) simulation . Moreover, while previous Raman and Fourier transform infrared (FTIR) spectroscopy studies have shown that the solvation structure of the redox species in bulk can be altered by spectator cations, much remains to be understood about how they influence the solvation environment at the electrified interface.…”
Section: Introductionsupporting
confidence: 78%
“… 40 Moreover, the electrostatic profile obtained from atomistic simulations reveals a complex, oscillatory and inhomogeneous behavior, highlighting the limitations of mean-field theories to treat complex interfaces. Combining MD simulation with theoretical modeling, Limaye et al 103 quantified the electrostatic potential fluctuations experienced by ionic species in the vicinity of an electrode surface and examined the role of image charge effects on such potential fluctuations.…”
Section: Representative Examplesmentioning
confidence: 99%
“…In order to comply with the peculiar geometry of the system, it is possible to use two-dimensional periodic boundary conditions (PBCs) using a modified Ewald treatment of electrostatic interactions . This approach was mostly used in the absence of redox reactions, i.e., to study the structure, the dynamics, and the capacitance of the electrochemical double-layer formed in nanoscale capacitors, albeit recent developments have allowed researchers to study the thermodynamics of electron transfer reactions in the vicinity of electrodes. On the other hand, the finite-field extended Lagrangian approach has been used in several classical and ab initio molecular dynamics (MD) studies of aqueous interfaces , (for a recent review see ref ). These simulations are carried out in a fully periodic three-dimensional MD cell using standard Ewald summation methods.…”
mentioning
confidence: 99%